Validalitas Saksi dalam Kajian Kitab Alfiyah Zubad pada Mata Pelajaran Kitab di Pondok Pesantren Raudlatul Muhibbin Al-Mustainiyyah Surakarta: Validity of Witnesses in the Study of the Book of Alfiyah Zubad in Book Subjects at the Raudlatul Muhibbin Al-Mustainiyyah Islamic Boarding School in Surakarta - Deny Fikriansah; Salman Lokollo; Muhammad Rizky Zidan (DIRASAH: Jurnal Kajian Islam, 2026)
This study aims to examine the concept of witness validity in Ibn Ruslan's Alfiyyah Zubad and its implementation in the study of the book at the Raudlatul Muhibbin Al-Mustainiyyah Islamic Boarding School in Surakarta. This study is important because the issue of testimony is one of the main aspects of Islamic law that is directly related to the upholding of justice and the moral integrity of the community. The research method used is a descriptive qualitative approach with data collection techniques through documenting the text of the book, indirect observation, and online communication with sources via WhatsApp. Primary data was obtained from the text of Alfiyyah Zubad and statements from ustadz and students, while secondary data came from various classical fiqh books, Islamic boarding school education books, and related scientific journals. The results of the study show that Ibn Ruslan emphasized two main requirements for witness validity, namely personal requirements and substantive requirements. Personal requirements include justice (‘adālah), honesty, the ability to provide consistent testimony, and freedom from personal interests. Meanwhile, substantive requirements require that testimony be given based on direct observation (musyāhadah) and not contradictory. The principle of caution in accepting testimony is also a characteristic of Islamic law, evident in the stipulations on the number of witnesses in cases of adultery and social transactions. Furthermore, research has found that the values ​​of fiqh (jurisprudence) regarding testimony in Alfiyyah Zubad are not only taught normatively but also internalized through the Islamic boarding school education process as part of the moral development of students.